Variation of horizontal stiffness of laminated rubber bearings using new boundary conditions - Ali Karbakhsh, Ravari; Ismail, Othman, Dr.; Zainah, Ibrahim, Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.